The Teaching Constraints of English as a Foreign Language in Indonesia: The Context of School Based Curriculum - Mattarima, Karim; Hamdan, Abdul Rahim (SOSIOHUMANIKA, 2011)
ABSTRACT: This article presents the teaching constraints of English as a Foreign Language (EFL) in the Indonesian Senior High School context outlined by the development of recent English curriculum (school based curriculum). It discusses teaching constraints of EFL speaking in recent school based curriculum, constraints on understanding learnersâ differences, constraints in learning material resources, constraints on classroom activities, constraints on teaching methods, and constraints on speaking assessment. Based on the discussion, this article also provides some solutions on what teachers of EFL speaking can do in order to achieve a higher quality of EFL speaking teaching and to improve the speaking skill of EFL students in Indonesia. Finally, the issue of the contribution of inserting learnersâ differences in curriculum design to promote independent or successful learners becomes important in the implementation of school-based curriculum as current curriculum with focusing on learner centered instruction in large and mixed ability class and in other old paradigms in EFL teaching and learning in Indonesia. Key words: Teaching constraints, English as a Foreign Language, learner differences, and school-based curriculum in Indonesia.Â Â About the Authors: Karim Mattarima is a Ph.D. Candidate at the Faculty of Education UTM (Technology University of Malaysia) in Johor Bahru, Johor, Malaysia; and Assoc. Prof. Dr. Abdul Rahim Hamdan is a Senior Lecturer at the Faculty of Education UTM. They can be reached at: karimmattarima@yahoo.co.idHow to cite this article? Mattarima, Karim & Abdul Rahim Hamdan. (2011). âThe Teaching Constraints of English as a Foreign Language in Indonesia: The Context of School Based Curriculumâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.4, No.2 [November], pp.287-300. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 4, 2011); Revised (October 7, 2011); and Published (November 20, 2011). Â  Â